Computational intelligence and predictive analysis for medical science : a pragmatic approach - Ahmad, Saif; Kumar, Praveen; Kumar, Praveen; Mohammadian, Masoud; Rawat, Seema; Tanwar, Poonam (Intelligent Biomedical Data Analysis ,, 2021)
This book uncovers stakes and possibilities offered by Computational Intelligence and Predictive Analytics to Medical Science. The main focus is on data technologies,classification, analysis and mining, information retrieval, and in the algorithms needed to elaborate the informations. A section with use cases and applications follows the two main parts of the book, respectively dedicated to the foundations and techniques of the discipline.